2013
DOI: 10.1002/lary.23900
|View full text |Cite
|
Sign up to set email alerts
|

Margin mapping in transoral surgery for head and neck cancer

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 44 publications
3
89
0
2
Order By: Relevance
“…However, transoral resection has been becoming more popular for head and neck cancer, especially for oropharyngeal and laryngeal caner. Hinni et al concluded that piecemeal removal of tumors with three-dimensional margin mapping using an operating microscope or rod telescope is safe from an oncologic standpoint, and reduces morbidity and length of hospital stay [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…However, transoral resection has been becoming more popular for head and neck cancer, especially for oropharyngeal and laryngeal caner. Hinni et al concluded that piecemeal removal of tumors with three-dimensional margin mapping using an operating microscope or rod telescope is safe from an oncologic standpoint, and reduces morbidity and length of hospital stay [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…712,15 TLM is a technique that can achieve the same in the oral cavity and other sites of the aerodigestive tract with minimal normal tissue disruption. 14,43 …”
Section: Discussionmentioning
confidence: 99%
“…Oncologically, Hinni et al [56], in a series of 129 tonsillar region SCC resected transorally, reported ≤ 1 cm resection margins in almost all cases, with a 99% 5-year local control estimate, a 94% recurrence-free survival estimate and a 76% overall survival estimate. In the largest series (111 T1, 132 T2) devoted to non-robotic transoral oropharyngectomy, local recurrence was independent of the site of origin (tonsil, anterior or posterior pillar), with a 89.9% and 85.8% 5-year local control estimate and a 97.2% and 93.2% overall local control estimate after salvage treatment in T1 and T2 SCC, respectively [10].…”
Section: Mandible-sparing Surgery In Early-stage Tonsillar Region Squmentioning
confidence: 96%
“…Over the last 15 years, several teams assessed mandible-sparing surgery in early-stage tonsillar region SCC, and with the introduction of the robotic techniques the transoral approach gained renewed interest [9,10,[50][51][52][53][54][55][56][57][58], the efficacy of which in terms of local control is independent of HPV status, as pointed out by Cohen et al [58].…”
Section: Mandible-sparing Surgery In Early-stage Tonsillar Region Squmentioning
confidence: 99%